Clinical Features, Risk Factors, and Therapy of Epithelial Keratitis after Cataract Surgery - Yani Wang; Dongfang Li; Wenjie Su; Yunhai Dai (Journal of Ophthalmology)
Purpose. The study aimed to assess the clinical characteristics, risk factors, and therapy of epithelial keratitis after cataract surgery. Methods. Medical data of 89 consecutive patients who developed epithelial keratitis after cataract surgery, including 37 patients with diabetes mellitus (37 eyes) and 52 patients without diabetes mellitus (52 eyes), were retrospectively reviewed. The clinical characteristics, risk factors, and therapy in those patients were evaluated. Results. The preoperative tear film function determined by the tear breakup time, meibomian gland atrophy score, and low tear meniscus height in diabetic patients was poorer than nondiabetic patients (P<0.001). Of diabetic patients, 83.78% (31/37) had been diagnosed with meibomian gland dysfunction before cataract surgery and treated with topical nonsteroidal anti-inflammatory drugs after cataract surgery for 44.69 ± 10.51 days, compared to 42.31% (22/52) of nondiabetic patients receiving the topical nonsteroidal anti-inflammatory treatment for 33.35 ± 5.16 days (both P<0.001). Epithelial lesions progressed within three to four days following cataract surgery in 59.46% (22/37) of diabetic patients, versus 30.77% (16/52) of the nondiabetic patients (P=0.025). Patients with combined meibomian gland dysfunction and epithelial defects accounted for 48.65% (18/37) in the diabetic group and 25.00% (13/52) in the nondiabetic group (P<0.001). In vivo confocal microscopy showed absence of subbasal never fibers in eyes with epithelial defects, and central corneal sensation was also significantly depressed in those eyes, but there was no significant difference between the two groups (P=0.227). Corneal ulceration and herpes simplex keratitis were found in 2.70% (1/37) and 5.41% (2/37) of diabetic patients, respectively. Amniotic membrane transplantation was required in 32.43% (12/37) of patients in the diabetic group, and the proportion was higher than 1.92% (1/52) in the nondiabetic group (P<0.001). Average healing time of the corneal epithelium in the diabetic group was 40.62 ± 20.0 days, much longer than 21.74 ± 6.94 days in the nondiabetic group (P=0.002). Conclusion. Epithelial keratitis after cataract surgery in diabetic patients has the characteristics of rapid development, severe epithelial damage, and slow repair of the corneal epithelium. Amniotic membrane transplantation is a good choice for persistent epithelial defects associated with such epithelial keratitis. Attention should be paid to the tear film function and use of topical nonsteroidal anti-inflammatory drugs in patients undergoing cataract surgery.